2006
DOI: 10.11613/bm.2006.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of duration of diabetes mellitus type 1 in children and adolescents on urinary N-acetyl-B-D-glucosaminidase excretion

Abstract: Jas min ka Ma ti ca, Viš nja Rač ki-Čar go nja, Šte fi ca Dvor nik KBC Ri je ka, Za vod za la bo ra to rij sku di jag nos ti ku, Ri je ka Uni ver si ty Hos pi tal Cen tre Ri je ka, De par tme nt of La bo ra to ry Diag nos ti cs, Ri je ka, Croa tia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
1
Order By: Relevance
“…9,[30][31][32] Studies have shown that u-NAG excretion increases even before microalbuminuria commences. 32,33 However in the present study, u-NAG activity was found to increase in parallel with MA, which is evident from significant positive correlation between NAG and MA. Our finding is in agreement with that reported by Cohen-Bucay A et al 34 The location and function of the brush-border membrane make it a good target for the primary involvement in the pathogenesis of diabetic renal complications.…”
Section: Discussioncontrasting
confidence: 64%
“…9,[30][31][32] Studies have shown that u-NAG excretion increases even before microalbuminuria commences. 32,33 However in the present study, u-NAG activity was found to increase in parallel with MA, which is evident from significant positive correlation between NAG and MA. Our finding is in agreement with that reported by Cohen-Bucay A et al 34 The location and function of the brush-border membrane make it a good target for the primary involvement in the pathogenesis of diabetic renal complications.…”
Section: Discussioncontrasting
confidence: 64%